2016
DOI: 10.3109/17518423.2015.1100689
|View full text |Cite
|
Sign up to set email alerts
|

Pictorial mnemonic-strategy interventions for children with special needs: Illustration of a multiply randomized single-case crossover design

Abstract: An innovative single-case crossover design containing multiple forms of randomization was implemented with eight participants in seven weekly sessions, during which instruction was given in the use of two different pictorial mnemonic (memory-enhancing) strategies: one designed to improve the children's learning of the dates of various inventions and the other designed to improve the children's acquisition of unfamiliar vocabulary items. A composite randomization statistical test revealed that when compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Between-and within-case (phase) intervention randomization, along with intervention start-point-randomization, would improve both the experimental control and statistical power of the study . For an actual research application and discussion of a combination of these three different randomization types, see the earlier referenced Hwang et al (2018) study.…”
Section: Four Types Of Single-case Interventionmentioning
confidence: 99%
See 2 more Smart Citations
“…Between-and within-case (phase) intervention randomization, along with intervention start-point-randomization, would improve both the experimental control and statistical power of the study . For an actual research application and discussion of a combination of these three different randomization types, see the earlier referenced Hwang et al (2018) study.…”
Section: Four Types Of Single-case Interventionmentioning
confidence: 99%
“…(For details on the tensions between the behavior analytic and statistical traditions, readers should refer to the early exchange between Edgington, 1980 a,b;and Kazdin, 1980.) In addition, in an actual SCI investigation, Hwang, Levin, and Johnson (2018) include an extensive discussion of these issues. We further believe that a SCI researcher's decision about whether to adopt design randomization is not a willy-nilly process.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A situation that incorporates aspects of Designs 2 and 3 was implemented in the previously cited Hwang et al (2016) study where, in the context of a single-case crossover design (Levin, Ferron, & Gafurov, 2014), four different learning strategies (two experimental and two control) were predicted to have similar effects on two different outcome measures. Moreover, in that single-case design, the outcome measures of interest were the amounts of change/improvement between the baseline (A) phase and the intervention (B) phase of the study.…”
Section: Design 4: Four Conditions Two Outcome Measuresmentioning
confidence: 99%
“…In the course of a recent research investigation-a single-case intervention study conducted by Hwang, Levin, and Johnson (2016)-we stumbled upon an interesting data-analysis situation that was reminiscent of one that had been considered a generation ago (Levin, Serlin, & Seaman, 1994). To summarize the take-home message of that 1994 article: Starting with a univariate K = 3 independent means one-way layout, we demonstrated that: (a) When an initial omnibus hypothesis test (of, for example, "All μ k are equal") is rejected based on a Type I error probability of α, (b) if any sub-hypothesis subsumed by the rejected hypothesis is tested at α, then (c) the resulting familywise Type I error probability (α FW ) associated with entire set of tested hypotheses is equal to α.…”
mentioning
confidence: 99%